Variable indoleamine 2,3‐dioxygenase expression in acral/mucosal melanoma and its possible link to immunotherapy - Iga, Natsuko; Otsuka, Atsushi; Hirata, Masahiro; Kataoka, Tatsuki R.; Irie, Hiroyuki; Nakashima, Chisa; Matsushita, Shigeto; Uchi, Hiroshi; Yamamoto, Yuki; Funakoshi, Takeru; Fujisawa, Yasuhiro; Yoshino, Koji; et al. (Cancer science, 2019)
Immune checkpoint inhibitors have improved the prognosis of advanced melanoma. Although anti–programmed death ligand‐1 (PD‐L1) is a well‐studied biomarker for response to anti–programmed death‐1 PD‐1 therapy in melanoma, its clinical relevance remains unclear. It has been established that the high expression of indoleamine 2,3‐dioxygenase (IDO) is correlated to a response to anti–CTLA‐4 treatment in melanoma. However, it is still unknown whether the IDO expression is associated with response to anti–PD‐1 therapy in advanced melanoma. In addition, acral and mucosal melanomas, which comprise a great proportion of all melanomas in Asians, are genetically different subtypes from cutaneous melanomas; however, they have not been independently analyzed due to their low frequency in Western countries. To evaluate the association of IDO and PD‐L1 expression with response to anti–PD‐1 antibody in acral and mucosal melanoma patients, we analyzed 32 Japanese patients with acral and mucosal melanomas treated with anti–PD‐1 antibody from the perspective of IDO and PD‐L1 expression levels by immunohistochemistry (IHC). Multivariate Cox regression models showed that the low expression of IDO in tumors was associated with poor progression‐free survival (HR = 0.33, 95% CI = 0.13‐0.81, P = 0.016), whereas PD‐L1 expression on tumors was not associated with progression‐free survival. Significantly lower expression of IDO in tumors was found in non–responders compared to responders. Assessment of the IDO expression could be useful for the identification of suitable candidates for anti–PD‐1 therapy among acral and mucosal melanomas patients. Further validation study is needed to estimate the clinical utility of our findings. Assessment of the IDO expression could be useful for the identification of suitable candidates for anti–PD‐1 therapy among acral and mucosal melanomas patients.